Interregionaal : verbindingsblad voor regionale werkgroepen. - Homo en Geloof Vlaanderen (Leuven : H&G Vlaanderen, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie
Nederlands
Periodiek